Predicting children's speech, language and reading impairment over time - Taylor, Catherine; Zubrick, Stephen (Sage, 2009)
Prospective population based longitudinal studies are highly informative for understanding developmental trajectories in speech, language and reading impairment. These studies contribute to our knowledge about the onset and trajectories of these disorders and to our understanding of the factors that influence these trajectories over the life course. Epidemiological research in speech, language and reading impairment shares some of the challenges inherent in studying any developmental impairment that persists yet changes over time. Not only do the speech, language and reading impairment phenotypes change over time but the proximal and distal factors associated with these phenotypes vary in magnitude at different epochs in development. The notion that phenotypes and the factors that influences them change is a positive one because it allows for the possibility of improvement and recovery. Clearly, the phenomenology of these developmental disorders makes the practical enterprise of identifying children at risk for these disorders and predicting their outcomes a significant challenge.